Application of a Computer-aid Diagnosis of Pneumoconiosis for CR X-ray Images - Abe, Koji; Minami, Masahide; Miyazaki, Ryosuke; Tian, Haiyan (British Journal of Healthcare and Medical Research, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This paper presents a method for applying a computer-aided diagnosis (CAD) for pneumoconiosis to chest X-ray images digitalized by the <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">computed radiography (CR) system<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">.<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">When we reported the CAD <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">before, we showed performance of the CAD for chest X-ray images digitalized by a CCD scanner. <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">However, since density distribution of the CR X-ray images is quite different from the images digitalized by CCD scanner, it is necessary to equip some preprocessing into the CAD for applying to the CR images. <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this paper, as the first trial for the application, drawing rib edges and additional lines on the CR images by a tablet PC, we examined whether the CAD can be interactively applied to the CR images. <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">U<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">sing 51 chest CR X-ray images, we compared the proposed CAD system with the existing system for the images digitalized by CCD scanner.